Developing an Integrity Policy for a Technical University: The Case of TU Delft. - Roeser, Sabine; Copeland, Samantha (Science & Engineering Ethics, 2026)
Integrity is an increasingly important topic at universities, due to more awareness as well as due to internal and external challenges. This paper tells the story of the development of the integrity infrastructure at Delft University of Technology in the Netherlands, a leading engineering university, We write this paper as academics and philosophers working at TU Delft and as members of the committees and working groups that, over the previous decade, took up the question of how to ensure integrity within our university. Thereby we also engaged with the question of what integrity at a university ought to be like as well as who has which responsibilities to support it. In this paper we will discuss key narrative themes that arose from the insights gained through this process. The intention in sharing this story is to guide fellow academics in similar positions, struggling to identify the needs of faculty, staff and students, who wish to act with integrity but who require institutional support and clear guidance to do so. In particular, we wish to highlight a key tension, between the need to formalise general basic requirements and the wish to have clear thresholds for good and bad behaviour, and the daily practice of integrity which requires context-sensitive awareness, respect, diversity, open-mindedness and continuous engagement with any principles laid down. We present our case through narrative form in order to trace both the points where and how this tension took form, and to note potential leverage points in such processes for others. The process of creating an integrity infrastructure, that is, both embodies and illustrates this tension as well as offering some ways to ease or accommodate it. Further, we present in this paper a key contribution of the integrity policy developed at TU Delft: the creation of an infrastructure and Code of Conduct that attend not only to academic integrity, but draw out and enact the responsibility frameworks and duties entailed by social and organizational integrity as well, which together constitute the three pillars of TU Delft's integrity policy. As academic integrity relates to issues such as research ethics, social integrity relates to behavior between people (employees and students), and organizational integrity relates to issues such as conflicts of interest and collaborations with external parties. Of course, challenging situations will often involve aspects that fall under more than one of these pillars, but the pillars help to provide conceptual clarity. In this way the integrity infrastructure developed at TU Delft is richer and more ambitious than policies that focus primarily on what we call 'academic integrity'.